Ответ(ы) на вопрос:
[latex]cos(\frac{\pi}{2}- \alpha )\cdot sin(\frac{\pi}{2}- \beta )-sin( \alpha - \beta )=sin \alpha \cdot cos \beta -sin( \alpha - \beta )=\\\\=\frac{1}{2}\cdot (sin( \alpha - \beta )+sin( \alpha + \beta ))-sin( \alpha - \beta )=\\\\=\frac{1}{2}sin( \alpha + \beta )-\frac{1}{2}sin( \alpha - \beta )=\frac{1}{2}\cdot (sin( \alpha + \beta )-sin (\alpha - \beta ))=\\\\=\frac{1}{2}\cdot 2\cdot sin\frac{2 \beta }{2}\cdot cos\frac{2 \alpha }{2}=sin \beta \cdot cos \alpha [/latex]
Не нашли ответ?
Похожие вопросы